Rilevare l'architettura in legno Protocolli metodologici per la documentazione delle architetture tradizionali lignee: i casi studio dei villaggi careliani in Russia - Porzilli, Sara (Premio Tesi di Dottorato, 2016)
This volume presents the research work carried out in the field of survey and representation methodologies for the documentation and analysis of wooden buildings. Thanks to the investigations carried out within a European project financed by the 7th Framework Program, several traditional Karelian villages, reported in this publication as case studies, have been documented with the aim of drawing guidelines for the development of suitable methodological protocols for documentation, analysis , survey, census and representation of complex systems. The research lays the foundations for the definition of an updated modus operandi to support the operators who are engaged in restoration, protection and preservation projects of the wooden architectural heritage.